The Effect of a Period Stretching Training on Functional Dynamic Balance Performance and Range of Motion Patients with Knee Osteoarthritis - Edris Bavardi Moghadam; Seyed Sadradin Shojaedin (Biyumikānīk-i varzishī)
Objective: This study was done to investigate the effect of a period of stretch training on functional dynamic balance performance and range of motion in patients with knee osteoarthritis. Methods: the population from which the sample of the study was selected included active older men with knee osteoarthritis in West Azerbaijan. 20 active man who were paid to exercise at least twice a week, were randomly divided into two groups of 10 patients. Subjects for 8 weeks, three times a week. To measure the functional dynamic balance three tests were used, and goniometer was used to measure the range of motion of the knee. To analyze the data, independent samples t-test was used for evaluating the between groups performance, and Paired samples t tests was used to check the within the group’s performance. Cohen's d-test was used to estimate the effect size. Results: Results of the study showed that there were significant differences within groups,  in Get Up and Go test (s) (p = 0.001), knee Range of motion, 30- Second Chair stand (the number) and Agility 8 foot time up and go for the elderly (s) (p = 0.0001). In between groups comparison also there were meaningful differences in Get Up and Go test (s) (p = 0.049), knee Range of motion, 30- Second Chair stand (the number) and Agility 8 foot time up and go for the elderly (s) (p = 0.0001). Conclusion: Stretch training can significantly improve functional dynamic balance and range of motion in active older men with knee osteoarthritis.